If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x-3(8x+6)=-18
We move all terms to the left:
8x-3(8x+6)-(-18)=0
We add all the numbers together, and all the variables
8x-3(8x+6)+18=0
We multiply parentheses
8x-24x-18+18=0
We add all the numbers together, and all the variables
-16x=0
x=0/-16
x=0
| 66+16t=30 | | 37-12=c-c | | 9^3x-1=27^4x | | (x+6)^2-8=41 | | X=22+.5x | | 6^4x-4=5 | | -20=8+6(x-9) | | r/12=12 | | 2x(2x)-9x-5=0 | | 2x+3x=1.5=12 | | q/6=3 | | 60+80x=100 | | y=5/7+4 | | x+13=2·(x-5) | | -24=-4(a+1) | | 2.5=-0.5b | | a*a*a+3*a+2=0 | | 192=4+x(x) | | 7x-9(2)=5x-8 | | 62+0=2x | | a*a+3*a+2=0 | | -1-7x=-85 | | 9^b=45 | | 7x-9x2=5x-8 | | x+6(×-4)=25 | | -4+4x=-4 | | 7x-9*2=5x-8 | | a*a+2*a+2=0 | | a^2+2*a+2=0 | | -6+d=18 | | 20=6(9x+7) | | 2(z+1)-3(z+2)=0 |